I'm reading Steele's The Cauchy-Schwarz Masterclass:

The first problem asks me to prove Cauchy's inequality:


I've tried to do it by creating a trivial instance of the inequality:

$$ab\leq \sqrt{a^2}\sqrt{b^2}$$

And then thinking about each side as a function:

$$f(a,b)=ab\quad\quad g(a,b)=\sqrt{a^2}\sqrt{b^2}$$

I can see that the image of $f$ is $\mathbb{R}$ while the image of $g$ is $\mathbb{R}_{\geq0}$ then when $a$ or $b$ are positive or negative, I can see that:

$$\begin{matrix} {}&{}&{f}&{g}\\ {-a}&{-b}&{ab}&{ab}\\ {-a}&{+b}&{-ab}&{ab}\\ {+a}&{-b}&{-ab}&{ab}\\ {+a}&{+b}&{ab}&{ab} \end{matrix}$$

And the case when $a\vee b=0$, for which $f=g=0$. Is it enough to prove this inequality? Am I missing something?

I've added more stuff, I have proved the case:


With the same reasoning, by making a function with both sides:

$$f(a_1,a_2,b_1,b_2)=a_1 b_1 + a_2b_2 \quad \quad g(a_1, a_2, b_1, b_2)=\sqrt{a_1^2+a_2^2}\sqrt{b_1^2+b_2^2}$$

And pointing that the domain of $f$ is $\mathbb{R}$ and the domain of $g$ is $\mathbb{R_{\geq 0}}$, from here I can deduce that the behavior will be the same for the functions:

$$f(a_1,a_2,b_1,b_2,\cdots , \cdots) \quad \quad g(a_1,a_2,b_1,b_2,\cdots, \cdots)$$

Thus giving values to the function, we can only have:

$$f=g \quad f < g$$

  • $\begingroup$ I do not understand what you are trying to do. How does this show the general case? $\endgroup$ – Calvin Lin Dec 7 '13 at 16:02
  • $\begingroup$ @CalvinLin Yes. I was also thinking about the same, I guess I just got an answer. I'll have lunch and I'll write when I get back. $\endgroup$ – Billy Rubina Dec 7 '13 at 16:04
  • 1
    $\begingroup$ Schwarz and Buniakovski are going to get mad: that inequality is a particular case of the Cauchy-Schwarz-Bunyakovski inequality. $\endgroup$ – DonAntonio Dec 7 '13 at 16:29
  • $\begingroup$ @CalvinLin Here it is. $\endgroup$ – Billy Rubina Dec 10 '13 at 11:23

Consider it to be like that:

$a=(a_1,a_2,...,a_n)$ and $b=(b_1,b_2,...,b_n)$. Then (real numbers)$<a,b>=|<a,b>|\leq \sqrt {<a,a>}\cdot \sqrt {<b,b>}$.

The proof of this is well known.

Hint:If $b=0$ then the proof is trivial.So suppose that $b\neq 0$.

Let $y=\frac {b}{\sqrt {<b,b>}}$. Then compute $<a-λy,a-λy>$ for a $λ\in \Bbb R$. Then by letting $λ=<a,y>$ see what you get from the computation of $<a-λy,a-λy>$.

  • 1
    $\begingroup$ I do not think the result you have written is much different from the question... I am confused.. $\endgroup$ – user87543 Dec 7 '13 at 16:21
  • $\begingroup$ @PraphullaKoushik,i agree. It's the the same.But the difference is that with inner product stuff you can do some tricks. $\endgroup$ – Haha Dec 7 '13 at 16:46

There are many ways of proving this. One way...

As the inequality is homogeneous in $a_i$, WLOG we can set $\sum a_i^2 = 1$. Similarly, we can set $\sum b_i^2 = 1$. Now we only have to prove:

$$\sum a_i b_i \le 1 \tag{1}$$

From $(a_i-b_i)^2 \ge 0$, we have $2a_i b_i \le a_i^2 +b_i^2$. Adding all of these, we get $(1)$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.